Combination of Different Laser Wavelengths as a Treatment Strategy for Maxillary Osteonecrosis: A Case Report: Laser therapy as treatment for maxillary osteonecrosis - Rocio Blanco Flórez, Pilar; Orozco Páez, Jennifer (Journal of Lasers in Medical Sciences, 2025)
Introduction: Osteonecrosis causes the death of bone tissue due to insufficient blood flow, which bdisrupts the supply of oxygen and nutrients, compromising the structural integrity of the bone. The jaws are particularly vulnerable due to their high bone turnover and vascularization. This study aimed to present the complex case of a patient diagnosed with maxillary osteonecrosis associated with osteomyelitis, treated exclusively with laser therapy. Case Report: We present the case of a 62-year-old male patient with maxillary osteonecrosis associated with osteomyelitis, manifested by an oroantral fistula located in the upper jaw. The treatment consisted of various laser therapy modalities, starting with the surgical phase on hard tissue for the excision of the necrotic bone (Er,Cr:YSGG 2780 nm laser), followed by photodynamic therapy (650 nm diode laser) for wound disinfection and intravascular laser irradiation of blood (ILIB) therapy (880 nm diode laser) in each session. Conclusion: The combination of different laser wavelengths was effective for the treatment of osteonecrosis.